Prospects and Challenges of Water Management Stakeholders in the Rural Communities of the Noun Division, West Region, Cameroon - Petiangma, Dereck Mbeh; Shende, Kometa Sunday; Fonteh, Niba Mary (Environmental Management and Sustainable Development, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Seven years after the formulation of the Sustainable Development Goals (SDGs), uncertainty looms on whether the 2030 targets would be achieved. In the Noun Division of Cameroon diverse stakeholders have made substantial efforts to meet the 2030 SDG on the provision of portable water to the rural communities. Despite these laudable efforts, access to portable water remains a topical issue in the Division. The focus of this study was to assess the prospects and challenges of water management stakeholders in the provision of portable water to the rural communities of the Noun Division. In order to meet this objective, a total of 400 questionnaires were randomly administered to household heads in rural councils with the help of traditional authorities. International, national, regional and local stakeholders involved in the management of water resources were interviewed. The “17 in 1” and “iQ. BAC” water test kits were respectively used to analyse the chemical properties of drinking water sources in situ and faecal content within 48 hours. Descriptive and inferential statistical techniques were used to analyse quantitative data while content and narrative analysis were used for qualitative data. Findings revealed that local, national and international portable water management stakeholders prioritised the improvement of portable water sources over other parameters. Whereas the proportion of people who depended on unimproved water sources reduced from 79.92% in 2015 to 57.52% in 2022, that with mean round trip time of over 30 minutes rather increased from 49.62% to 50.38%. Moreover, 50% of the interviewee indicated that portable water is expensive in the area, suggesting why 42.3% of the population still rely on streams today. Five sampled streams analysed with the iQ. BAC test kit tested positive for total coliform while confirmatory laboratory analysis revealed E. coli concentration of 11-100MPN/100ml in Njimom which according to WHO is synonymous to medium risk. The “17 in 1” test kit revealed abnormal concentration of lead (0.03-0.05 ppm) and sulphate (400-800 ppm) mainly in streams and boreholes. PCA identified five main components that account for 72.71<strong style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">%<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> variance in the hydrochemistry of drinking water sources. Though, none of the four scenarios developed revealed complete access to improve drinking water in rural areas of the Noun Division by 2030, Njimom and Foumbot showed remarkable progress under the most probable scenario (50% increase in current effort) considered to be the most realistic. Water governance stakeholders should quadruple their current efforts in improving portable water sources and adopt a holistic approach that engulfs water quality improvement if they wish to make significant progress on SDG 6.1.